Simulating arsenic migration in arid farmland soils under high-arsenic groundwater irrigation in Xinjiang - Jiale He; Wenwen Deng; Tuerxun Tuerhong; Yanli Luo; Meijuan Wang; Zhen Song; Xuan Liu; Xinzhe Xie; Qian Zhang; Enmeng Yu; Rui Sun (PLoS ONE, 2026)
Arsenic (As) is a toxic element widely distributed in the environment. A simulation irrigation experiment was conducted to investigate the migration characteristics of As(V) in farmland soils of the Kuitun River Basin, Xinjiang, under different irrigation scenarios. Irrigation water quality was simulated by altering evaporation intensities, pH values and TDS. Changes in As content in the soil solution were then analyzed. Ion exchange membranes were inserted directly into the soil to visualize As distribution in the soil profile, and the As adsorbed on the membranes was analyzed via SEM-EDS, providing spatial distribution information that corroborated the quantitative measurements of As in soil solution, thereby achieving visualization of As distribution within the soil profile. The results indicated that all three factors significantly influenced the distribution of As(V) in the top 0–10 cm of the soil layer. Under weak evaporation conditions, As migrated further both vertically and horizontally in the soil profile. Conversely, increasing the pH and salt content of the irrigation water promoted the downward penetration of As from the topsoil. These findings suggest that in the arid agricultural region, irrigation with less saline and alkaline groundwater may immobilize As effectively in the top soil layers and mitigate the potential risks associated with As soil contamination.